Growth under Different Trophic Regimes and Synchronization of the Red Microalga Galdieria sulphuraria - Náhlík, Vít (Biomolecules, 2021)
The extremophilic unicellular red microalga Galdieria sulphuraria (Cyanidiophyceae) is able to grow autotrophically, or mixo- and heterotrophically with 1% glycerol as a carbon source. The alga divides by multiple fission into more than two cells within one cell cycle. The optimal conditions of light, temperature and pH (500 µmol photons m(−2) s(−1), 40 °C, and pH 3; respectively) for the strain Galdieria sulphuraria (Galdieri) Merola 002 were determined as a basis for synchronization experiments. For synchronization, the specific light/dark cycle, 16/8 h was identified as the precondition for investigating the cell cycle. The alga was successfully synchronized and the cell cycle was evaluated. G. sulphuraria attained two commitment points with midpoints at 10 and 13 h of the cell cycle, leading to two nuclear divisions, followed subsequently by division into four daughter cells. The daughter cells stayed in the mother cell wall until the beginning of the next light phase, when they were released. Accumulation of glycogen throughout the cell cycle was also described. The findings presented here bring a new contribution to our general understanding of the cell cycle in cyanidialean red algae, and specifically of the biotechnologically important species G. sulphuraria.